Preparation of micro/nanometer-sized porous surface structure of calcium phosphate scaffolds and the influence on biocompatibility. Issue 10 (22nd May 2014) - Gao, Chengde; Zhuang, Jingyu; Li, Pengjian; Shuai, Cijun; Peng, Shuping
Abstract: Abstract : Multilayer stereo micro/nanometer-sized porous surface structures were prepared by selective chemical etching of biphasic calcium phosphate (BCP) scaffolds with hydroxyapatite (HAP)/β-tricalcium phosphate (β-TCP) weight ratios of 90/10, 80/20, 70/30, 60/40, and 50/50 in phosphoric acid solution. The porous surface structures revealed periodic fluctuations in the observed heights of micro/nanometer-sized needles. And the average height increased from 0.59 ± 0.02 to 12.09 ± 0.03 μm when the β-TCP content in BCP scaffolds rose from 10 to 50%. In vivo cell tests using MG-63 cells (belonging to the human osteosarcoma cell line) revealed that micro/nanometer-sized pores on the scaffold surface could provide location for cell adhesion and migration and facilitate the formation of gap junction between cells. The BCP scaffold with 40% β-TCP exhibited the optimal surface structure for cell seeding and growth due to the largest number of micro/nanometer-sized pores on the surface. However, excessive β-TCP led to the damage of micro/nanometer-sized porous surface structure, which further impeded the cell interaction.